Potassium phthalimide as efficient basic organocatalyst for the synthesis of 3,4-disubstituted isoxazol-5(4H)-ones in aqueous medium - Hamzeh Kiyani; Fatemeh Ghorbani (Journal of Saudi Chemical Society)
Potassium phthalimide (PPI) is employed as an efficient and effective basic organocatalyst for the one-pot three-component reaction of β-oxoesters with hydroxylamine hydrochloride and various aromatic aldehydes. This cyclocondensation reaction was performed in water as an environmentally benign solvent at room temperature giving 3,4-disubstituted isoxazol-5(4H)-ones in good to excellent yields. PPI was found to be an effective organocatalyst for the synthesis of isoxazol-5(4H)-one system. The advantages of this method are efficiency, clean, easy work-up, high yields, shorter reaction times, inexpensive, and readily available catalyst.